Moving Bodies: Creative Infrastructures of Identification - Sara Casartelli (Tecnoscienza, 2021)
This article empirically analyses how the unknown bodies of migrants who died in the attempt to reach Europe are managed and potentially identified. Shifting attention away from the border, the paper provides a new angle to the crisis unfolding in the Mediterranean, investigating the practices developed in order to know and attend to the dead migrant’s body. More specifically, drawing from 6 months of ethnographic fieldwork conducted in Sicily in 2016 and 2017, the article presents an ethnographic account of the emergent Italian forensic infrastructure. It does so by looking at movement. The movement of bodies towards identification. The pursuit is informed by Science and Technology Studies (STS); the focus is on material practices aimed at the eventual identification of unknown bodies. Taking stock from recent debates in the anthropology of infrastructure in which scholars critique the idea that infrastructures are passive architectures comprising circulations, the paper proposes an alternative perspective on infrastructures, arguing that infrastructures are processes of constant and creative adjustment and that these ongoing changes are the effect of circulation.